Folkevalgt og politisk leder - Røiseland, Asbjørn; Vabo, Signy Irene (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"The premise of Elected Officials and Political Leaders is that every elected politician is a political leader. This anthology looks at political leadership in Norwegian local governments and explores how to understand this form of leadership. Passing resolutions is an important part of an elected official's job, and public discourse can suggest that such work is itself the essence of political leadership. This is a central concern in the book, which argues that political leadership also consists of grasping and understanding issues, setting agendas, proposing solutions and mobilizing support for them. With this broad view of political leadership, the book is organized around four paradoxes associated with the political-administrative system in Norwegian municipal government: the conflict paradox, the administration paradox, the transparency paradox and the democracy paradox. The chapters describe and discuss these paradoxes, the tensions they are based on and how opposing interests can be balanced in a constructive way, both for the local public sector as a whole as well as the individual councils and councilors. The book provides examples of how elected leaders can strengthen their political leadership, not least through a systematic comparison with Danish municipal governments. Important points in each chapter are also emphasized in interviews with political and administrative leaders who share their experiences with the authors. The book concludes with a discussion of how political leadership can be further developed and strengthened, both through changes in the institutional framework for Norwegian local governments and through dialogue and reflection within the individual municipal councils."